Laminated Flow-Cell Detector with Granulated Scintillator for the Detection of Tritiated Water - Dixon, Nile E. J.; Monk, Stephen D.; Graham, James; Cheneler, David (Radiation (Multidisciplinary Digital Publishing Institute), 2023)
Nuclear sites require regular measurements of the air, soil, and groundwater to ensure the safety of the surrounding environment from potentially hazardous levels of contamination. Although high-energy beta and gamma emitters can often be detected instantly using fixed dosimeters, the detection of low-energy beta emitters is a difficult challenge, especially in groundwater, as its radiation is easily self-absorbed by the surrounding medium. Therefore, it is common practice to sample groundwater and transfer it to a laboratory for analysis using Liquid Scintillation Counting. This work demonstrates a new detector design for the real-time monitoring of tritiated water, a weak beta emitter. This design utilizes a flow cell filled with a granulated scintillator to maximize the surface area of the sample. The cavity is made from plastic sheets, which allow rapid manufacture using readily available lamination sheets. A column of SiPMs in coincidence counting mode has been implemented to reduce noise and allow future extensions to the flow cell for greater detection rates while allowing the detector to fit within limited spaces such as groundwater monitoring boreholes. Using multiple concentrations of tritiated water, this detector has been validated and calibrated, obtaining a minimum detection activity of 26.356 ± 0.889 Bq/mL for a 1-day counting period.